2004
DOI: 10.20870/oeno-one.2004.38.1.932
|View full text |Cite
|
Sign up to set email alerts
|

Vine and water: a short review

Abstract: <p style="text-align: justify;">Water is an important factor in the terroirs of grape-growing regions. The vine obtains water from rainfall and the water table and when it is in short supply, it is necessary either to irrigate or accept the effects of water stress. Depending on the intensity of the water stress and the period at which it occurs, it may or not be favourable for the harvest and the wine it is used to produce. The objective of this article is to provide some information on the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 25 publications
5
110
1
20
Order By: Relevance
“…Furthermore, the greater trunk height in GDC system (1.90 m) as compared to VSP (1.0 m) and also the differences in branch orientation could have contributed to hinder water transport to the grapevine canopy. Schubert et al (1999) showed that shoot hydraulic conductivity is negatively affected by downward branch orientation in contrast with upward growing (Deloire et al, 2004), the photosynthesis was unaffected as shown by other authors for grapevine (Souza et al, 2005b) and other crop species (Fereres and Soriano, 2007). The differences between seasons of CO 2 assimilation rates were probably due to weather conditions (temperatures) during gas exchange measurements, as explained above for results of leaf water potential.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…Furthermore, the greater trunk height in GDC system (1.90 m) as compared to VSP (1.0 m) and also the differences in branch orientation could have contributed to hinder water transport to the grapevine canopy. Schubert et al (1999) showed that shoot hydraulic conductivity is negatively affected by downward branch orientation in contrast with upward growing (Deloire et al, 2004), the photosynthesis was unaffected as shown by other authors for grapevine (Souza et al, 2005b) and other crop species (Fereres and Soriano, 2007). The differences between seasons of CO 2 assimilation rates were probably due to weather conditions (temperatures) during gas exchange measurements, as explained above for results of leaf water potential.…”
Section: Resultsmentioning
confidence: 50%
“…Moreover, the Ψ stem can be a powerful tool to assess vine water status since it is less affected by shortterm fluctuations induced by stomatal behavior and environmental conditions as compared to Ψ md (Choné et al, 2001). Despite the differences for Ψ pd values of the 2007 season, they were above -0.2 MPa in both management systems, which is in the range considered as absence of water stress, whereas in 2008 season the values were around -0.4 MP, considered as a mild water stress (Deloire et al, 2004). The differences between seasons may be explained by evapotranspiration and by the interval between irrigation and measurements of pre-dawn leaf water potential.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Esta diferencia se puede deber a la metodología de medición, ya que evaluaciones con cámara de presión tipo Scholander tradicional es fácil cometer errores en la lectura, debido a que la presión es regulada con una válvula que fácilmente puede entregar más presión a la cámara, si la experiencia del operario no es la adecuada, entregando valores más negativos que los reales, con mayor facilidad cuando se requiere menos presión para la determinación del potencial hídrico. Esta puede ser la explicación de por qué algunos investigadores (Sellés et al, 2002;Deloire et al, 2004;López, 2005;Girona et al, 2006) catalogan a vides en condición óptima de riego con valores de xm más negativos; xm < -1 MPa.…”
Section: Resultados Y Discusiónunclassified